The Role Of Women Factory Workers In Increasing Family Income (Case Study : PT Java Mete Indonesia, Demak Regency) - Amanda Mastisia Rakanita (Institute of Computer Science (IOCS), 2021)
This study aims to determine the role of female factory workers in increasing family income with working hours as an intervening variable. Family income in this study is represented by the income of women laborers and dependents who also work and generate income. This type of research uses a quantitative approach. The population in this study consists of 75 female workers at PT Java Mete Indonesia with the sampling technique using simple random sampling. Data was collected using a questionnaire. This study used quantitative analysis with multiple linear regression and testing of partial line-of-analysis (t test) and path analysis for partial variable testing (t test). Research results indicate that. (1) The variable income of female workers has a positive and significant effect on the working hours variable. (2) The insurance variable has a negative and insignificant effect on the working hours variable. (3) The income variable of women workers has a positive and significant effect on the family income variable. (4) The dependent variable has a positive but insignificant effect on the family income variable, (5) The working hour variable has a positive and significant effect on the family income variable, (6) The female labor income variable has the family income variable mediated by the working hour variable resulting in an indirect effect on the income of female workers by mediating working hours. (7) Dependent variable on family income mediated by working hours variable shows that indirectly dependents mediating working hours have no significant effect on family income.